Penerapan Metode Concept Sentence untuk Meningkatkan Kemampuan Menulis Teks Pidato Persuasif - Sari, Mona; Sarno R. Sudibyo; Ina Asnurani (UIN Raden Mas Said Surakarta, Indonesia, 2022)
The skills of writing persuasive speech texts for class IX students of SMP Negeri 4 Semende Darat Tengah need to be improved. This is due to the low ability of students to write persuasive speeches. The low ability to write persuasive speeches is caused by internal and external factors. Internal factors are factors that come from students, in the form of lack of confidence, low ability to assemble words, and express ideas. External factors are factors from outside the students themselves including methods in delivering material in the form of lecture methods and assignments that cause students to feel bored and do not pay attention to each stage of learning activities properly. To improve students' ability to write persuasive speeches, the concept sentence method is used. The concept sentence method can be used to improve Indonesian language learning outcomes, especially in the lesson of writing persuasive speech texts for class IX students of SMP Negeri 4 Semende Darat Tengah semester 1 of the 2021/2022 academic year. Keterampilan menulis teks pidato persuasif peserta didik kelas IX SMP Negeri 4 Semende Darat Tengah perlu dilakukan peningkatan. Hal tersebut disebabkan oleh kemampuan peserta didik menyusun teks pidato persuasif tergolong rendah. Rendahnya keterampilan menyusun teks pidato persuasif disebabkan faktor dari dalam dan dari luar peserta didik. Faktor dari dalam adalah faktor dari dalam diri peserta didik, berupa kurangnya rasa percaya diri, rendahnya kemampuan merangkai kata, dan menuangkan gagasan. Sedangkan faktor dari luar peserta didik adalah faktor yang berasal bukan dari peserta didik, faktor ini terdiri dari metode dalam menyampaikan materi berupa metode ceramah dan penugasan yang menyebabkan peserta didik merasa jemu dan kurang memperhatikan setiap tahapan kegiatan pembelajaran dengan baik. Untuk menambah keterampilan menulis teks pidato persuasif peserta didik maka digunakan metode concept sentence. Metode concept sentence dapat dipakai untuk meningkatkan hasil belajar Bahasa Indonesia terutama pada pelajaran menulis teks pidato persuasif peserta didik kelas IX SMP Negeri 4 Semende Darat Tengah semester 1 tahun ajaran 2021/2022.